HIGH EXPECTATIONS FOR HIGHER EDUCATION? PERCEPTIONS OF COLLEGE AND EXPERIENCES OF STRESS PRIOR TO AND THROUGH THE COLLEGE CAREER. - KREIG, DANA BALSINK (College Student Journal)
Increasing numbers of students are experiencing difficulty adjusting to college. Violated expectations of college may increase the stress experienced across the college career. Therefore, 36 college students were assessed prior to matriculation, during the first year and during the senior year. Expectations and experiences of academics, social life, family involvement, and satisfaction with the chosen college were compared. Students' experiences generally did not differ from their expectations, except regarding increased involvement with family. Violated expectations of academic demands predicted stress during the first and senior years. Violated expectations regarding social experiences predicted stress in the vulnerable first year.